GSAP-ERE: Fine-Grained Scholarly Entity and Relation Extraction Focused on Machine Learning - Otto, Wolfgang; Gan, Lu; Upadhyaya, Sharmila; Karmakar, Saurav; Dietze, Stefan (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Research in Machine Learning (ML) and AI evolves rapidly. Information Extraction (IE) from scientific publications enables to identify information about research concepts and resources on a large scale and therefore is a pathway to improve understanding and reproducibility of ML-related research. To training and testing of IE models focused on fine-grained information in ML-related research, e.g. method training and data usage, we introduce GSAP-ERE. It is a manually curated fine-grained dataset of mentions of 63K ML-related entities and 35K relations distributed across 10 entity types and 18 semantically categorized relation types annoated in the full text of 100 ML publications. We show that our dataset enables fine-tuned models to automatically extract ML-related information that facilitate knowledge graph (KG) construction from scholarly papers or monitoring of computational reproducibility of AI research at scale. Additionally, we use our dataset as a test suite to explore prompting strategies for IE using Large Language Models (LLM). We observe that the performance of state-of-the-art LLM prompting methods is largely outperformed by our best fine-tuned baseline model (NER: 80.6%, RE: 54.0% for the fine-tuned model vs. NER: 44.4%, RE: 10.1% for the LLM). This disparity of performance between supervised models and unsupervised usage of LLMs suggests datasets like GSAP-ERE are needed to advance research in the domain of scholarly information extraction.